Nowcast of an EUV dynamic spectrum during solar flares. (1st September 2020) - Kawai, Toshiki; Imada, Shinsuke; Nishimoto, Shohei; Watanabe, Kyoko; Kawate, Tomoko
Abstract: In addition to X-rays, extreme ultraviolet (EUV) rays radiated from solar flares can cause serious problems, such as communication failures and satellite drag. Therefore, methods for forecasting EUV dynamic spectra during flares are urgently required. Recently, however, owing to the lack of instruments, EUV dynamic spectra have rarely been observed. Hence, we develop a new method that converts the soft X-ray light curve observed during large flare events into an EUV dynamic spectrum by using the Solar Dynamics Observatory / Atmospheric Imaging Assembly images, a numerical simulation, and atomic database. The simulation provides the solution for a coronal loop that is heated by a strong flare, and the atomic database calculates its dynamic spectrum, including X-ray and EUV irradiances. The coefficients needed for the conversion can be calculated by comparing the observed soft X-ray light curve with that of the simulation. We apply our new method to three flares that occurred in the active region 12673 on September 06, 2017. The results show similarities to those of the Flare Irradiance Spectral Model, and reconstruct some of the EUV peaks observed by the EUV Variability Experiment onboard the Solar Dynamics Observatory . Highlights: A new method to convert a soft X-ray light curve into an EUV dynamic spectrum during flares is presented. The conversion can be calculated via a numerical simulation and an atomic database. It succeeds in reconstructing some EUV peaks in the observed dynamic spectrum.